WATER AS THE IDEAS FOR KERIS CREATION - Muhammad Ra'uf Dwi Fajri; Bening Tri Suwasono (ARTISTIC : International Journal of Creation and Innovation, 2023)
Water is a natural element that inspires artistic creation. Water is crucial for life. Almost all organisms inhabit habitats ecosystems with sufficient water availability. Water as a source of inspiration in the creation of this artwork is embodied in the dhapurkeris. This work uses the Mor-Jo-Si-Ngun aesthetic approach, with exploration, design, and embodiment serving as its production method. There are three keris made with the names dhapurTirtaPanguripanluk-7, TirtaSegara luk-5, and TirtaAwang-awang. Each created work carries a meaning according to the title and philosophy of water as a symbol of life.